2018
DOI: 10.2147/ott.s164430
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary relapse of acute lymphoblastic leukemia after allogeneic hematopoietic stem cell transplantation treated by CAR T-cell therapy: a case report

Abstract: Philadelphia chromosome-positive (Ph-positive) acute leukemia (ALL) accounts for around one quarter of adult cases of ALL and is usually associated with poor prognosis. The patients still encounter a high rate of relapse even after they receive hematopoietic stem cell transplantation (HSCT). HSCT is considered the established therapy and best option for many malignant ALL cases, however, disease relapse remains the main reason of failure. In recent years, chimeric antigen receptor (CAR) T-cell therapy has beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The 1 patient with testicular relapse underwent orchiectomy before infusion of tisagenlecleucel and had no measurable disease in his BM. Trafficking of the CAR-T cells was not directly analyzed in this patient; however, CAR-T therapy has been shown to reach non-CNS sites of EM disease, such as the cervix, breast, and bone, as well as testes [16][17][18][19], and this patient did have grade 1 CRS, suggesting possible CAR-T-mediated effects.…”
Section: Discussionmentioning
confidence: 94%
“…The 1 patient with testicular relapse underwent orchiectomy before infusion of tisagenlecleucel and had no measurable disease in his BM. Trafficking of the CAR-T cells was not directly analyzed in this patient; however, CAR-T therapy has been shown to reach non-CNS sites of EM disease, such as the cervix, breast, and bone, as well as testes [16][17][18][19], and this patient did have grade 1 CRS, suggesting possible CAR-T-mediated effects.…”
Section: Discussionmentioning
confidence: 94%
“…Another report showed a GVL effect of blinatumomab in relapsed ALL patients after allo-HCT [24]. More importantly, beneficial effects of chimeric antigen receptor T cell therapy have been also reported in an ALL patient with EMR after allo-HCT [25]. The role of immune therapy has also been recently strengthened by the experience with novel immune therapies that were introduced into the treatment of advanced hematologic malignancies.…”
Section: Discussionmentioning
confidence: 98%
“…Wang and colleagues reported that extramedullary ALL relapse in the cervix manifesting as a solid mass after allo-HSCT could be completely removed by CAR T-cell therapy [14], thus suggesting that CAR-T cells possess a highly penetrating and eradicating ability when encountering extramedullary leukemia mass. Due to a large number of capillaries, CAR-T cells should be able to infiltrate the skin and reach leukemia cells acting as subcutaneous nodules facilitated by the capillary transportation and working more efficiently, which was supported by the present case where skin nodules were significantly diminished (Fig.1a, c, d).…”
Section: Discussionmentioning
confidence: 99%